2012
DOI: 10.1088/0256-307x/29/11/114206
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Oxide-Based Q-Switched Fiber Laser with Stable Five-Wavelength Operation

Abstract: We demonstrate an erbium-doped ring-cavity fiber laser Q-switched by a graphene oxide-based saturable absorber (GOSA). The GOSA was fabricated by vertically evaporating GO-polyvinylalcohol (GO/PVA) composite dispersion, and has a good performance under room temperature. Utilizing a specially fabricated fiber Bragg grating (FBG), stable five-wavelength lasing is realized and stabilized at different pump powers under any polarization state. When the pump power increases from 78.4 mW to 379.3 mW, the output power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The carbon-based nano-materials e.g. graphene 14 , graphene-oxide 15,16 , and carbon nanotube 17 have attracted great research interests for its demonstrated exceptional nonlinear optical responses. However, these carbon-based materials have their own limitations e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The carbon-based nano-materials e.g. graphene 14 , graphene-oxide 15,16 , and carbon nanotube 17 have attracted great research interests for its demonstrated exceptional nonlinear optical responses. However, these carbon-based materials have their own limitations e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the graphene used in many experiments was prepared by the chemical reduction process of graphene oxide (GO) [129]. Furthermore, graphene oxide is widely used in Yb-doped fiber lasers.…”
Section: Yb-doped Fiber Lasersmentioning
confidence: 99%
“…The Q-switching is one of the successful methods. [6,7] Another way to increase per-pulse energy is to lower the repetition rate of mode-locked lasers by using a modulator as a pulse picker. [8] However, reduction of the repetition rate in this way introduces significant energy loss and a complex configuration.…”
Section: Introductionmentioning
confidence: 99%